Solutions of General Equilibrium Problems for a Trading World - Helpman, Elhanan (Econometrica, 1976)
[Defining each good (factor) in each different country as a distinct good (factor), one can use Scarf's algorithm to solve general equilibrium problems for a trading world. The dimension of such problems grows very fast with the number of goods (factors) and countries, making computations extremely costly. Here we present a method for solving general equilibrium problems for a trading world which can be applied to a class of problems, and which requires considerably less computation time than the direct application of Scarf's algorithm.]